Analysis of the need for a mobile application to support family caregivers of patients with incurable cancer – The development of the “Angehörigen-App”: a qualitative study in Switzerland - Beat Huber; Natalie Röderer; Monica Fliedner; Alexander Wünsch (Swiss Medical Weekly)
BACKGROUND: The prevalence of cancer is rising continuously worldwide. Relatives play an important role in caring for cancer patients and are at the same time affected by the illness and treatment of their loved ones. They have often been referred to as a forgotten group. Advances in digital technology offer various opportunities to enhance the well-being of and care for relatives.